A Novel Approach to E-Voting With Group Identity-Based Identification and Homomorphic Encryption Scheme - Vangujar, Apurva K.; Ganesh, Buvana; Umrani, Alia; Palmieri, Paolo (IEEE access, 2024)
This article presents a novel e-voting scheme that combines Group Identity-based Identification (GIBI) with Homomorphic Encryption (HE) based on the discrete logarithmic assumption. The proposed scheme uses the Schnorr-like GIBI scheme for voter identification and authorization using zero-knowledge proofs to ensure the anonymity and eligibility of voters. The voter v_{i,j} is granted the authorization to cast a valid vote for a single candidate C_{k} . The use of distributed ElGamal provides fairness while the use of partial shares for decryption enables individual and universal verifiability without the need for a central authority. The proposed scheme is secure under various scenarios and robust in the random oracle model. The GIBI-HE scheme offers a promising solution for e-voting, providing a sustainable and accessible environment for voters while supporting the unreusability of votes and protecting the privacy of voters.